SENI PEDALANGAN DALAM PENJAJAGAN MASA DEPAN - Suwondo Suwondo (Institut Seni Indonesia Surakarta, 2007)
Puppetry or the shadow puppet performance has gone into a decrease in its qualiry and .frequency. This transformation, of course, has positive and negative impacts. The present puppetry has little chance of being a source of lift guidance for the Javanese. Unlike puppetry in the past, puppetry as ordinary entertainment does not take the balance between entertainment and guidance into consideration and is market-oriented which entertains instantaneouslY so long as it is new and salable. The importance is that it is livelY and funny and if it is necessary it does not matter when it creates a pornographic impression. The shadow puppet peiformance has changed into a commodiry or merchandise.Keywords: Puppetry, commodity, transformation